Androgenic Modulation in the Primary Ovarian Growth of the Japanese eel, Anguilla japonica - Shang-Chien, Lee (Zool Stud, 2019)
Anguilla japonica seedling production is urgently required for eel aquaculture due to the species’ severely dwindling population. This study aimed to understand androgenic modulation of the primary ovarian growth, a critical development phase in females, in this semelparous fish. Through histological analysis, primordial to primary follicle transition was observed before hormone injection, and eels injected with SPH + MT showed greater synchronous follicle development than those injected with SPH alone. An in vivo experiment revealed a positive correlation (p < 0.05, r = 0.94) between the mRNA expression of arα and increasing gonadal somatic index (GSI) < 0.75% before SPH injection. Another positive correlation was seen between arβ expression and GSI (p < 0.05, r = 0.97) after weekly SPH injections for three weeks. fshr expression was high in the SPH + MT-injected group. Significantly high fshr mRNA levels were found after weekly MT injections for two weeks (p < 0.05), whereas the expression levels dropped after flutamide injection. arα and arβ expressions revealed different patterns before and after SPH induction. In this study, androgen modulation was found with regard to ARs expressions during primary growth and the primordial to primary follicle transition prior to hormone induction. This modulation continuously affected fshr expression and vitellogenic development after SPH induction during ovarian growth in the Japanese eel.